Chronic low back pain and physical activity among patients within the Brazilian National Health System: a cross-sectional study - Zanuto, Everton Alex Carvalho; Fernandes, Rômulo Araújo; Turi-Lynch, Bruna Camilo; Castoldi, Robson Chacon; Morais, Luana Carolina de; Silva, Pedro Victor Tonicante da; Codogno, Jamile Sanches (São Paulo Medical Journal, 2020)
BACKGROUND: This study was based on filling a gap in our knowledge regarding the issue of what the protective effect of physical exercise on patients within the Brazilian National Health System could be, in relation to low back pain. OBJECTIVES: To determine the prevalence of chronic low back pain (CLBP) and to analyze the protective effect of physical exercise among patients over 50 years old attended at primary healthcare units (PHUs). DESIGN AND SETTING: Analytical cross-sectional study at Universidade Estadual Paulista (UNESP) that was conducted in two PHUs (Parque Cedral and Vila Real), located in different regions of the city of Presidente Prudente, Brazil. METHODS: In total, 327 patients were interviewed and evaluated at which retrospective characteristics covering the previous 12 months. The Nordic questionnaire was used to classify CLBP, and the Baecke questionnaire for physical activity level. The body mass index (kg/m2) was calculated using body mass and height values, both collected at the time of the interview. RESULTS: High prevalence of low back pain was found; 175 patients (53.5%) reported having had at least one episode of low back pain in the previous year. Of these, 71 (21.7%) answered yes to all four questions on the Nordic questionnaire and were classified as CLBP. Physical exercise remained associated with CLBP, independent of other factors (odds ratio = 0.35; 95% confidence interval = 0.15-0.80). CONCLUSION: High prevalence of low back pain was identified among PHU users. Physical exercise was associated as an independent protective factor against this pathological condition.